TINJAUAN YURIDIS TERHADAP KEWENANGAN ORANG TUA ADOPSI DALAM MEMBERIKAN HARTA KEKAYAAN TERHADAP ANAK ADOPSI - Alfian Aziz (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstractThe presence of the baby into a most beautiful gift in the world that is felt for many married couples. With the presence of the baby will certainly add to the completeness and perfection in our lives. But what would happen if at a wedding who stepped in first, second to third but has not given the baby.The distribution of inheritance is generally not done secra formal, but with the deliberations witnessed by village officials. By way of deliberation is intended that all issues can be resolved by peaceful means. In talking about the division of inheritance is one thing that will not be missed is the talk about everything pertaining to the rights and obligations of the heir or adopted children.Therefore, the adoption of a child act in Indonesia more and more people do, then the need for immediate formulation of laws concerning the adoption of a child. This is necessary so that the uniformity and no differences primarily related to inheritance for adopted children conducted by the adoptive parents.